Analisis Metode Benefit Cost Analysis (BCA) Dalam Audit Sistem Informasi PT. Najwa Bintang Anugerah - Mumtas, Fuad (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Nowadays the technology in the business world is very important in determining the progress of a company. Misuse of the use of the application system can occur. System Application and Product (SAP), which is a high-tech Enterprise Resource Planning (ERP) and is widely used by large companies, especially in Indonesia. Misuse of the use of the application system can occur. And to anticipate the emergence of problems related to data management in the future and for now, we need a system that can minimize the obstacles that occur. As a follow-up to the findings resulting from the audit results, the company invests in implementing improvements or enhancements to the management of the use of information systems. The company must consider whether the investment for improvement or improvement in the management is acceptable or not. Due to this, the results of the information system audit are combined using Benefit Cost Analysis (BCA).